2019
DOI: 10.1002/pc.25328
|View full text |Cite
|
Sign up to set email alerts
|

Impact of lithium chloride on the performance of wood fiber reinforced polyamide 6/high‐density polyethylene blend composites

Abstract: Wood fiber reinforced polyamide 6 (PA6) and high‐density polyethylene (HDPE) blend composites were prepared via hot pressing. The PA6 was modified by lithium chloride (LiCl) for reducing the melting point. Crystallization analysis exhibited the decrease of the melting point (220°C to none) and the processing temperature (240°C to 200°C) of PA6. Thus, undesired discoloration and degradation were improved. LiCl was in favor of the interfacial compatibility among PA6, HDPE, and wood fiber. Also the LiCl could enh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 36 publications
0
2
0
Order By: Relevance
“…The identification was carried out by SEM equipped with an energy-dispersive X-ray spectroscopy (EDS) detector (the respective EDS spectra are presented in the Supplementary Information, Figure S3 ). Experimental studies reported in the literature have shown that even the low amounts of lithium chloride (0.5 wt%) present in the polymer sample exhibit plasticizing properties [ 63 , 64 ]. The presence of lithium chloride is manifested by lowering the melting point and the crystallinity of a polymer.…”
Section: Resultsmentioning
confidence: 99%
“…The identification was carried out by SEM equipped with an energy-dispersive X-ray spectroscopy (EDS) detector (the respective EDS spectra are presented in the Supplementary Information, Figure S3 ). Experimental studies reported in the literature have shown that even the low amounts of lithium chloride (0.5 wt%) present in the polymer sample exhibit plasticizing properties [ 63 , 64 ]. The presence of lithium chloride is manifested by lowering the melting point and the crystallinity of a polymer.…”
Section: Resultsmentioning
confidence: 99%
“…[1][2][3] Parts of the traditional petroleum-based polymers are gradually replaced by degradable plastics, bio-based polymers, and wood plastic composites (WPCs), and so forth. [4][5][6] WPCs sourced from the waste thermoplastic polymers and natural fibers, are extensively used in the fields of building, transportation, and consumption. [7][8][9] As the commodity thermoplastics, high-density polyethylene (HDPE), polypropylene (PP), and polyvinyl chloride (PVC) had applicable mechanical properties, favorable processability, good resource availability, and high price-performance.…”
Section: Introductionmentioning
confidence: 99%